COVID-19 and income inequality: Evidence from monthly population registers - Nikolay Angelov; Daniel Waldenström (Institute of Labor Economics (IZA), 2021)
We measure the distributional impact of the COVID-19 pandemic using newly released population register data in Sweden. Monthly earnings inequality increased during the pandemic, and the key driver is income losses among low-paid individuals while middle- and high-income earners were almost unaffected. The pandemic had a larger negative impact on private-sector workers and on women. Using data on individual take-up of government COVID-19 support, we show that policy significantly dampened the inequality increase, but did not fully offset it. Annual total market income inequality, which also includes capital income and taxable transfers, shows similar patterns of increasing inequality during the pandemic.
Keywords: D31; H12; H24; J22; 330; pandemic; income inequality; earnings; government policy; COVID-19